Preparation method of silicoaluminophosphate molecular sieve fluidized bed catalyst
By modifying titanate on the silicon aluminum phosphate molecular sieve and preparing the fluidized bed catalyst in combination with high-speed shear and spray drying technology, the problems of catalyst wear resistance and selectivity are solved, and efficient and low-cost catalytic performance is achieved.
Patent Information
- Application Number
- CN202311221775.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-21
AI Technical Summary
The existing silicon-aluminum phosphate molecular sieve fluidized bed catalysts have poor wear resistance and low selectivity of ethylene and propylene.
By treating the silica aluminum phosphate molecular sieve in an alcohol solution containing titanate, the modified molecular sieve is formed, and mixed with liquid medium, matrix material and binder to form a suspension. After high-speed shearing and spray-drying, the catalyst is finally calcined.
The prepared catalyst has high wear resistance and high ethylene and propylene selectivity, and does not significantly increase production costs while ensuring catalytic performance.
Smart Images

Figure CN119680633A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalyst preparation, and in particular to a method for preparing a silicoaluminophosphate molecular sieve fluidized bed catalyst. Background Art
[0002] Ethylene and propylene are the cornerstones of the chemical industry. The development of coal chemical olefin preparation technology routes using coal or natural gas as raw materials has important practical significance for balancing the supply and demand of low-carbon olefins, reducing dependence on crude oil imports, and promoting national energy security.
[0003] Methanol-To-Olefin (MTO) refers to the process technology of using methanol, which is usually produced from natural gas or coal, to produce polymerization-grade ethylene, propylene and other low-carbon olefins under the action of catalysts. In the MTO process, when the finished fluidized bed catalyst enters the reaction-regeneration system for continuous cyclic catalytic reaction, the constant collision and friction between the catalysts, between the catalysts and the reactor tube wall, between the catalysts and the transportation pipeline, and between the catalysts and the regeneration system make it difficult to avoid the wear of the catalyst. Catalyst wear includes two mechanisms, one is catalyst surface abrasion, and the other is catalyst rupture. If the catalyst strength is poor, it will be severely worn in the reaction-regeneration system. In order to maintain the catalyst reserve in the system, more fresh catalysts need to be continuously added during the reaction process, which will increase production costs; too much catalyst fine powder entering the water treatment system will also cause frequent blockage of the water treatment system, increasing the production burden. Therefore, in order to reduce the wear of the catalyst in the fluidized bed reactor, the catalyst is required to have good anti-wear performance. In some cases, improving the wear resistance of the catalyst will reduce the catalytic performance of the catalyst. For example, if the catalyst calcination temperature is increased, the structure of the catalyst microspheres calcined at high temperature will be more dense, which will improve its wear resistance. However, the dense structure will lead to a decrease in diffusion performance, which will reduce the selectivity of ethylene and propylene in the MTO reaction. On the other hand, the reduction of the production cost of MTO fluidized bed catalyst is also an issue worthy of attention. It has been reported that the method of improving the wear resistance of the catalyst by spray drying twice will increase the energy consumption of catalyst production, which is not conducive to the control of catalyst production costs.
[0004] CN102527445A discloses a method for preparing a low-wear fluidized bed microsphere catalyst, wherein molecular sieve, adhesive, dispersant and water are prepared into a slurry, spray-dried after shearing, the obtained microsphere particles are redispersed in water and shear-sprayed again, and then the microsphere particles are roasted to obtain a low-wear fluidized bed catalyst. CN103769237A discloses a method for improving the wear resistance of a fluidized bed catalyst, wherein catalyst fine powder with an average particle size of less than 80 microns is uniformly mixed with molecular sieve, adhesive, carrier material and liquid medium to form a suspension, and the suspension is sheared at high speed and spray-dried to effectively improve the wear resistance of the finished catalyst. CN101157057A discloses a method for preparing a low-wear catalyst by synthesizing molecular sieves in situ, wherein porous microspheres are first prepared by spray molding, and then the microspheres are subjected to hydrothermal synthesis treatment to generate an ordered molecular sieve structure inside the porous microspheres, thereby obtaining a low-wear microsphere catalyst. CN107971024A discloses a method for preparing a highly wear-resistant fluidized bed catalyst. A suspension obtained by mixing a molecular sieve, a binder, a carrier material and a liquid medium is spray-dried to obtain a microsphere catalyst. The microsphere catalyst is dispersed in a solution containing aluminum oxide and spray-dried again. The catalyst strength is improved by wrapping a layer of aluminum oxide with relatively high hardness on the outer layer of the catalyst.
[0005] In summary, although some existing patents involve the issue of improving the wear resistance of fluidized bed catalysts, the wear resistance of fluidized bed catalysts still needs to be further improved, while also taking into account that the catalytic performance of the catalyst does not decrease and the production energy consumption does not increase. Summary of the invention
[0006] The technical problem to be solved by the present invention is that the existing technology has the problem that the silicoaluminophosphate molecular sieve fluidized bed catalyst has poor wear resistance and low selectivity for ethylene and propylene, and provides a method for preparing the silicoaluminophosphate molecular sieve fluidized bed catalyst. The catalyst prepared by the method has the characteristics of high wear resistance and good selectivity for ethylene and propylene.
[0007] The first aspect of the present invention provides a method for preparing a silicoaluminophosphate molecular sieve fluidized bed catalyst, comprising:
[0008] a) treating the silicoaluminophosphate molecular sieve in an alcohol solution containing titanate, and drying to obtain a modified molecular sieve;
[0009] b) mixing the modified molecular sieve obtained in step a), a liquid medium, a matrix material and a binder to form a suspension;
[0010] c) high-speed shearing the suspension obtained in step b) and spray drying to obtain a microsphere catalyst;
[0011] d) calcining the microsphere catalyst obtained in step c) to obtain the catalyst.
[0012] According to one aspect of the present invention, the treatment method in step a) is to mix and stir the silicoaluminophosphate molecular sieve and the alcohol solution containing titanate in a certain weight ratio and then treat. The weight ratio of the molecular sieve to the alcohol solution containing titanate is 10-40:100, preferably 10-30:100, the treatment temperature is 30-90°C, preferably 50-90°C, and the treatment time is 30-90 minutes, preferably 30-50 minutes.
[0013] According to one aspect of the present invention, after the treatment in step a), conventional filtering and washing operations are first performed and then drying is performed. The drying conditions are: temperature of 80-130° C. and time of 0.5-12 hours.
[0014] According to one aspect of the present invention, the silicoaluminophosphate molecular sieve in step a) is washed with water and then subjected to solid-liquid separation before being treated with the alcohol solution containing titanate, and the obtained solid is not dried.
[0015] According to one aspect of the present invention, deionized water is added to the alcohol solution containing titanate, and the weight ratio of titanate, alcohol and water satisfies the following ratio: titanate:alcohol=1-4:100, deionized water:alcohol=1-5:100.
[0016] According to one aspect of the present invention, the titanate is selected from at least one of tetrabutyl titanate and tetraisopropyl titanate, preferably tetrabutyl titanate (purity ≥ 98 wt %).
[0017] According to one aspect of the present invention, the alcohol is selected from at least one of ethanol and isopropanol, preferably ethanol.
[0018] According to one aspect of the present invention, the silicoaluminophosphate molecular sieve is selected from at least one of SPAO-34 and SPAO-18, preferably SAPO-34 molecular sieve; the Si / Al molar ratio of the SAPO-34 molecular sieve is 0.05-0.5:1, and the Si / Al molar ratio of the SPAO-18 molecular sieve is 0.1-0.3.
[0019] According to one aspect of the present invention, in the suspension of step b), calculated by weight ratio: the molecular sieve is preferably 5-40 wt %; the binder is preferably 1-20 wt %; the matrix material is preferably 5-50 wt %; and the liquid medium is preferably 10-89 wt %.
[0020] According to one aspect of the present invention, in the suspension of step b), calculated by weight ratio: the molecular sieve is more preferably 10-30 wt %; the binder is more preferably 1-10 wt %; the matrix material is more preferably 10-40 wt %; and the liquid medium is more preferably 15-79 wt %.
[0021] According to one aspect of the present invention, the solid content of the suspension in step b) is preferably 20-50%, and the pH value is preferably 2.5-5.5.
[0022] According to one aspect of the present invention, in step b), the binder is a sol, the matrix material is clay and / or hydrotalcite, and the liquid medium is deionized water.
[0023] According to one aspect of the present invention, the binder in step b) is preferably silica sol or alumina sol; the matrix material is clay and / or hydrotalcite, preferably at least one selected from kaolin, bentonite and hydrotalcite, more preferably kaolin.
[0024] According to one aspect of the present invention, in step c), the high-speed shearing is performed until 90% of the particles in the mixed liquid have a size of less than 5 microns.
[0025] According to one aspect of the present invention, the conditions for spray drying in step c) are: inlet temperature of 180-300° C., outlet temperature of 100-160° C., and centrifugal speed of 5000-15000 rpm.
[0026] According to one aspect of the present invention, in step d), the calcination temperature is 500-900°C, preferably 550-750°C, the calcination time is 0.5-24 hours, preferably 4-12 hours, and the calcination atmosphere is a flowing atmosphere, preferably flowing air, and the flow power comes from the negative pressure.
[0027] According to one aspect of the present invention, the catalyst prepared by spray drying has a wear index of less than 1.00 wt% / h after high-temperature calcination, preferably a wear index of less than 0.50 wt% / h, more preferably a wear index of less than 0.30 wt% / h, and more preferably a wear index of 0.20-0.25 wt% / h.
[0028] According to one aspect of the present invention, the average particle size of the catalyst prepared in step d) is 70-130 microns, preferably 80-110 microns.
[0029] According to one aspect of the present invention, in the catalyst prepared in step d), the content of TiO2 calculated as Ti is 0.500%-1.500% based on the weight of the catalyst.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The silicoaluminophosphate molecular sieve fluidized bed catalyst of the present invention has high catalytic performance and low wear index, and is applied to the methanol to olefin reaction, and has the characteristics of high selectivity for low-carbon olefins and low wear index. Under the premise of ensuring the catalytic performance of the MTO fluidized bed catalyst, the production cost of the catalyst is not significantly increased, and a fluidized bed catalyst with high wear resistance is obtained.
[0032] 2. The crystal size of the silicoaluminophosphate molecular sieve prepared by the prior art hydrothermal synthesis method is only a few hundred nanometers. In the drying process of the original molecular sieve powder, the molecular sieve crystals with high surface energy are very easy to agglomerate. The agglomerated molecular sieve crystals in the spray-formed catalyst microspheres, due to the local stress difference caused by the uneven distribution between the molecular sieve and the matrix material, can reduce the wear resistance of the catalyst. In the present invention, before the silicoaluminophosphate molecular sieve is dried, the surface of the molecular sieve is modified with tetrabutyl titanate, and the modified molecular sieve is not easy to agglomerate. In the pulping process of the catalyst spray drying, a more uniform slurry can be obtained, thereby obtaining a silicoaluminophosphate fluidized bed catalyst with a lower wear index. In addition, the TiO2 generated by the titanate located on the surface of the molecular sieve crystal grains after calcination can reduce the microscopic stress between the crystal grains and the matrix material, and improve the grain boundary bonding strength, which is also one of the reasons why the catalyst prepared by the present invention has higher wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the XRD spectrum of the SAPO-34 molecular sieve obtained in Preparation Example 5;
[0034] Figure 2 This is the XRD spectrum of the SAPO-18 molecular sieve obtained in Example 9;
[0035] Figure 3 This is a SEM photograph of the silicoaluminophosphate molecular sieve fluidized bed catalyst obtained in Example 1. DETAILED DESCRIPTION
[0036] The wear index of the present invention is measured on a D5757-11 fluidized bed abrasion tester of VINCI Company, and is measured using the method of Chapter 7 of Q / SH 361.552-2017.
[0037] In the present invention, the wear index ω is expressed in mass fraction per hour (% / h) and is calculated according to the following formula:
[0038]
[0039] Where:
[0040] m5——the mass of the powder collection system after 5 hours, in grams (g);
[0041] m1——the mass of the powder collection system after 1 hour, in grams (g);
[0042] m——the numerical value of the sample mass, in grams (g);
[0043] m0——the mass of the powder collection system before the test, in grams (g);
[0044] 4——The unit is h.
[0045] The arithmetic mean of the two determination results is taken as the analysis result and rounded off according to the provisions of GB / T 8170 to an accuracy of 0.01% / h.
[0046] The average particle size of the catalyst of the present invention is measured by a laser particle size analyzer (model: Malvern 2000).
[0047] The morphology of the catalyst of the present invention is measured using a Philips XL300 scanning electron microscope.
[0048] The Ti content in the catalyst of the present invention is tested by ICP, instrument parameters: Varian 725ES, test method: standard curve method. Test conditions are shown in Table 1:
[0049] Table 1
[0050] name Technical Parameters name Technical Parameters Plasma power 1100W Injection time 45s Plasma gas (Ar) <![CDATA[15L min -1 ]]> Reading time 5s Auxiliary gas (Ar) <![CDATA[1.5L min -1 ]]> Injection pump speed 15rpm Nebulizer flow rate <![CDATA[0.75L min -1 ]]> Observation Mode Radial Observation height 10mm Ti measurement wavelength 336.122nm
[0051] The present invention has no particular limitation on the high-speed shearing, which can be performed according to conventional technical means in the art, and the present invention will not elaborate on it here.
[0052] The present invention will be described in detail below through examples.
[0053] The reagents in the following examples are commercially available and of analytical grade.
[0054] [Preparation Example 1]
[0055] This preparation example is used to illustrate the preparation of the tetrabutyl titanate ethanol solution of the present invention:
[0056] Weigh 100 parts of ethanol solution and 4 parts of tetrabutyl titanate by weight, add the tetrabutyl titanate dropwise into the ethanol solution under stirring, weigh 5 parts of deionized water, add into the above solution and continue stirring until it is uniform.
[0057] [Preparation Example 2]
[0058] This preparation example is used to illustrate the preparation of the tetrabutyl titanate ethanol solution of the present invention:
[0059] Weigh 100 parts of ethanol solution and 1 part of tetrabutyl titanate by weight, add the tetrabutyl titanate dropwise into the ethanol solution under stirring, weigh 2 parts of deionized water, add into the above solution and continue stirring until it is uniform.
[0060] [Preparation Example 3]
[0061] This preparation example is used to illustrate the preparation of the tetrabutyl titanate ethanol solution of the present invention:
[0062] Weigh 100 parts of ethanol solution and 2 parts of tetrabutyl titanate by weight, add the tetrabutyl titanate dropwise into the ethanol solution under stirring, weigh 3 parts of deionized water, add into the above solution and continue stirring until it is uniform.
[0063] [Preparation Example 4]
[0064] This preparation example is used to illustrate the preparation of the isopropyl titanate isopropanol solution of the present invention:
[0065] Weigh 100 parts of ethanol solution and 2 parts of isopropyl titanate by weight, add isopropyl titanate dropwise into the isopropyl alcohol solution under stirring, weigh 3 parts of deionized water, add into the above solution and continue stirring until it is uniform.
[0066] [Preparation Example 5]
[0067] This preparation example is used to illustrate the preparation of the SAPO-34 molecular sieve described in the present invention:
[0068] 12.0 parts of γ-Al2O3 and 35.0 parts of deionized water were weighed and mixed evenly to form a solution a; 23.1 parts of phosphoric acid (85 weight %) and 37.5 parts of deionized water were mixed evenly to form a solution b; a and b were mixed and stirred at room temperature for 2 hours to form a uniform solution c; while maintaining stirring, 20.2 parts of triethylamine, 15 parts of tetraethylammonium hydroxide TEAOH, 4.5 parts of silica sol (40 weight %) and 10.0 parts of deionized water were added to c in sequence, and mixture A was obtained after sufficient stirring.
[0069] Mixture A was placed in a crystallization kettle and heated to 200°C under stirring. After crystallization for 24 hours, the solid product was recovered by solid-liquid separation. The solid product was washed three times with deionized water and then dried. XRD characterization showed that the obtained product was pure phase SAPO-34 (Si / Al molar ratio was 0.15).
[0070] [Preparation Example 6]
[0071] This preparation example is used to illustrate the preparation of the silicoaluminophosphate molecular sieve fluidized bed catalyst of the present invention:
[0072] Weigh the raw materials according to the ratio of 16% (weight) SAPO-34 molecular sieve; 20% (weight) kaolin; 4% (weight) aluminum sol; 60% (weight) deionized water. Except for water, the raw material ratios here are all dry weight ratios. First, mix the SAPO-34 molecular sieve with a certain amount of water, stir for 1 hour, and then high-speed shear for 15 minutes; add aluminum sol, stir quickly for 15 minutes, and high-speed shear for 15 minutes; add kaolin, stir for 30 minutes, and then high-speed shear mixing for 45 minutes to obtain a suspension (solid mass content is 38%, pH value is 4.2). It is determined that 90% of the particle size in this suspension is less than 3.9 microns. The suspension is spray-dried (inlet temperature is 290°C, outlet temperature is 140°C, and centrifugal speed is 10,000 rpm), and then calcined at 600°C for 6 hours under air conditions to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0073] [Example 1]
[0074] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed with deionized water for 3 times and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 1 at a weight ratio of 20:100 without drying. The mixture was stirred at 60°C for 30 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 6 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0075] The SAPO-34 molecular sieve, kaolin, aluminum sol and deionized water were weighed in a weight ratio of 16:20:4:60, and mixed, spray-dried and calcined according to the method described in Preparation Example 6 to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0076] The average particle size and TiO2 content of the catalyst obtained in Example 1 are shown in Table 2.
[0077] [Example 2]
[0078] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed three times with deionized water and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 1 at a weight ratio of 20:100 without drying. The mixture was stirred at 30°C for 30 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate, and dried at 110°C for 6 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0079] The SAPO-34 molecular sieve, kaolin, aluminum sol and deionized water were weighed in a weight ratio of 16:20:4:60, and mixed, spray-dried and calcined according to the method described in Preparation Example 6 to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0080] The average particle size and TiO2 content of the catalyst obtained in Example 2 are shown in Table 2.
[0081] [Example 3]
[0082] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed three times with deionized water and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 1 at a weight ratio of 20:100 without drying. The mixture was stirred at 90°C for 30 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate, and dried at 110°C for 6 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0083] The SAPO-34 molecular sieve, kaolin, aluminum sol and deionized water were weighed in a weight ratio of 16:20:4:60, and mixed, spray-dried and calcined according to the method described in Preparation Example 6 to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0084] The average particle size and TiO2 content of the catalyst obtained in Example 3 are shown in Table 2.
[0085] [Example 4]
[0086] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed with deionized water for 3 times and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 1 at a weight ratio of 40:100 without drying. The mixture was stirred at 90°C for 30 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 8 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0087] The SAPO-34 molecular sieve, kaolin, aluminum sol and deionized water were weighed in a weight ratio of 16:20:4:60, and mixed, spray-dried and calcined according to the method described in Preparation Example 6 to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0088] The average particle size and TiO2 content of the catalyst obtained in Example 4 are shown in Table 2.
[0089] [Example 5]
[0090] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed three times with deionized water and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 2 at a weight ratio of 15:100 without drying. The mixture was stirred at 90°C for 60 minutes, and the solution was filtered out. The obtained solid was washed once with ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 8 hours to obtain the titanate-modified SAPO-34 molecular sieve.
[0091] The SAPO-34 molecular sieve, kaolin, aluminum sol and deionized water were weighed in a weight ratio of 16:20:4:60, and mixed, spray-dried and calcined according to the method described in Preparation Example 6 to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0092] The average particle size and TiO2 content of the catalyst obtained in Example 5 are shown in Table 2.
[0093] [Example 6]
[0094] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed three times with deionized water and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 2 at a weight ratio of 10:100 without drying. The mixture was stirred at 60°C for 45 minutes, and the solution was filtered out. The obtained solid was washed once with ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 8 hours to obtain the titanate-modified SAPO-34 molecular sieve.
[0095] The SAPO-34 molecular sieve, kaolin, aluminum sol and deionized water were weighed in a weight ratio of 16:20:4:60, and mixed, spray-dried and calcined according to the method described in Preparation Example 6 to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0096] The average particle size and TiO2 content of the catalyst obtained in Example 6 are shown in Table 2.
[0097] [Example 7]
[0098] The SAPO-34 molecular sieve prepared by hydrothermal synthesis in Preparation Example 5 was separated from the solid and liquid. The obtained solid product was washed three times with deionized water and then added to the tetrabutyl titanate ethanol solution obtained in Preparation Example 3 at a weight ratio of 30:100 without drying. The mixture was stirred at 70°C for 45 minutes, and the solution was filtered out. The obtained solid was washed once with an ethanol solution to remove free tetrabutyl titanate and dried at 110°C for 6 hours to obtain a titanate-modified SAPO-34 molecular sieve.
[0099] The SAPO-34 molecular sieve, kaolin, aluminum sol and deionized water were weighed in a weight ratio of 16:20:4:60, and mixed, spray-dried and calcined according to the method described in Preparation Example 6 to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0100] The average particle size and TiO2 content of the catalyst obtained in Example 7 are shown in Table 2.
[0101] [Example 8]
[0102] Compared with Example 1, the only difference is that the tetrabutyl titanate ethanol solution in Preparation Example 1 is replaced by the tetraisopropyl titanate isopropanol solution in Preparation Example 4.
[0103] The average particle size and TiO2 content of the catalyst obtained in Example 8 are shown in Table 2.
[0104] [Example 9]
[0105] Compared with Example 1, the only difference is that the SAPO-34 molecular sieve is replaced by a SAPO-18 molecular sieve (Si / Al molar ratio is 0.15).
[0106] The average particle size and TiO2 content of the catalyst obtained in Example 9 are shown in Table 2.
[0107] [Comparative Example 1]
[0108] Using the SAPO-34 molecular sieve of Preparation Example 5, the raw materials are weighed according to the ratio of 16% (weight) SAPO-34 molecular sieve; 20% (weight) kaolin; 4% (weight) aluminum sol; 60% (weight) deionized water. Except for water, the raw material ratios here are all dry weight ratios. First, the SAPO-34 molecular sieve is mixed with a certain amount of water, stirred for 1 hour, and then sheared at high speed for 15 minutes; aluminum sol is added, stirred rapidly for 15 minutes, and sheared at high speed for 15 minutes; kaolin is added, stirred for 30 minutes, and then sheared at high speed for 45 minutes to obtain a suspension (solid mass content is 38%, pH value is 4.2). It is determined that 90% of the particle size in this suspension is less than 3.9 microns. The suspension is spray-dried (same as Example 1), and then calcined at 600°C for 6 hours under air conditions to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0109] The average particle size and TiO2 content of the catalyst obtained in Comparative Example 1 are shown in Table 2.
[0110] [Comparative Example 2]
[0111] Compared with Comparative Example 1, the only difference is that all dry basis weights in the spray slurry of Comparative Example 1 are regarded as 100 parts, 6 parts by weight of tetrabutyl titanate are additionally added, and the newly prepared slurry is spray dried and calcined to obtain a silicoaluminophosphate molecular sieve fluidized bed catalyst.
[0112] The average particle size and TiO2 content of the catalyst obtained in Comparative Example 2 are shown in Table 2.
[0113] [Test Example 1]
[0114] The fluidized bed catalysts obtained in Examples 1-9 and Comparative Examples 1-2 were respectively tested for wear index using a D5757-11 fluidized bed abrasion tester. The results are shown in Table 3.
[0115] [Test Example 2]
[0116] The silicoaluminophosphate molecular sieve catalysts obtained in Examples 1-9 and Comparative Examples 1-2 were respectively used for methanol to olefins reaction on a small fixed fluidized bed. The reaction conditions were: 40 g catalyst, pure methanol feed, mass space velocity (WHSV) 4 h -1 , reaction temperature 480°C, reaction pressure normal pressure. The reaction results are shown in Table 3.
[0117] Table 2
[0118]
[0119]
[0120] Table 3
[0121]
[0122] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a silicoaluminophosphate molecular sieve fluidized bed catalyst, comprising: a) treating the silicoaluminophosphate molecular sieve in an alcohol solution containing titanate, and drying to obtain a modified molecular sieve; b) mixing the modified molecular sieve obtained in step a), a liquid medium, a matrix material and a binder to form a suspension; c) high-speed shearing the suspension obtained in step b) and spray drying to obtain a microsphere catalyst; d) calcining the microsphere catalyst obtained in step c) to obtain the catalyst.
2. The preparation method according to claim 1, characterized in that: The treatment method in step a) is to mix and stir the silicoaluminophosphate molecular sieve and the alcohol solution containing titanate in a certain weight ratio and then treat them, wherein the weight ratio of the molecular sieve to the alcohol solution containing titanate is 10-40:100, preferably 10-30:100, the treatment temperature is 30-90°C, preferably 50-90°C, and the treatment time is 30-90 minutes, preferably 30-50 minutes.
3. The preparation method according to claim 2, characterized in that: The silicoaluminophosphate molecular sieve prepared in step a) is washed with water and then subjected to solid-liquid separation before being treated with the titanate ethanol solution, and the obtained solid is not dried.
4. The preparation method according to claim 1 or 2, characterized in that: Deionized water is added to the alcohol solution containing titanate, and the weight ratio of titanate, alcohol and water satisfies the following ratio: titanate:alcohol=1-4:100, and deionized water:alcohol=1-5:
100.
5. The preparation method according to claim 1, characterized in that: The titanate is selected from at least one of tetrabutyl titanate and tetraisopropyl titanate, preferably tetrabutyl titanate; the alcohol is selected from at least one of ethanol and isopropanol, preferably ethanol; the silicoaluminophosphate molecular sieve is selected from at least one of SPAO-34 and SPAO-18, preferably SAPO-34 molecular sieve; the Si / Al molar ratio of the SAPO-34 molecular sieve is 0.05-0.5:1, and the Si / Al molar ratio of the SPAO-18 molecular sieve is 0.1-0.
3.
6. The preparation method according to claim 1, characterized in that: In step b), in the suspension, calculated by weight ratio: the molecular sieve is 5-40% by weight, preferably 10-30% by weight; the binder is 1-20% by weight, preferably 1-10% by weight; the matrix material is 5-50% by weight, preferably 10-40% by weight; the liquid medium is 10-90% by weight, more preferably 15-80% by weight.
7. The preparation method according to claim 1 or 6, characterized in that: Step b) the solid content of the suspension is 20-50% by weight and the pH value is 2.5-5.5; And / or, in step c), high-speed shearing is performed until 90% of the particles in the mixed liquid have a size of less than 5 microns.
8. The preparation method according to claim 1, characterized in that: Step b) The binder is a sol, preferably a silica sol or an alumina sol; the matrix material is clay and / or hydrotalcite, preferably at least one selected from kaolin, bentonite and hydrotalcite, more preferably kaolin; and the liquid medium is deionized water.
9. The preparation method according to claim 1, characterized in that: In step d), the calcination temperature is 500-900° C., preferably 550-750° C., the calcination time is 0.5-24 hours, preferably 4-12 hours, and the calcination atmosphere is flowing air.
10. The preparation method according to claim 1, characterized in that: After high-temperature calcination, the catalyst prepared by spray drying has an attrition index of less than 1.0 wt% / h, preferably less than 0.50 wt% / h, and more preferably less than 0.30 wt% / h.
11. The preparation method according to claim 1, characterized in that: The average particle size of the catalyst prepared in step d) is 70-130 microns, preferably 80-110 microns.
12. The preparation method according to claim 1, characterized in that: In the catalyst prepared in step d), the content of TiO2 calculated as Ti is 0.500%-1.500% based on the weight of the catalyst.
Citation Information
Patent Citations
A method for synthesizing oxygen-containing compound conversion olefinic hydrocarbon microspherical catalyst
CN101157057A
Preparation method of low-abrasion fluidized bed microspherical catalyst
CN102527445A
Method for improving wear-resisting property of fluidized bed catalyst
CN103769237A
Fluidized bed catalyst preparation method
CN107971024A
Titanium modified SAPO-34 molecular sieve and preparation method and application thereof
CN101898768A